Implementation of an Advanced Practice Physiotherapy Clinical Placement in Paediatric Rheumatology: A Case Report. - Herrington, Julie; Li, Hank; Beattie, Karen; Robarts, Susan; Rushton, Alison; Dhir, Jasdeep (Physiotherapy Canada, 2026)
Purpose: To describe the implementation and reflections of an entry-level physiotherapy student clinical placement with an advanced physiotherapist practitioner (APP) in paediatric rheumatology. Method: A 7-week physiotherapy clinical placement consisting of 2 days/week supervised by an APP and 3 days/week supervised by a traditional physiotherapist was offered to a student in an entry-level Master of Science (MSc) Physiotherapy (PT) programme. Results: Student performance assessments included a learning contract and the Assessment of Clinical Performance tool. Final assessment in the traditional physiotherapy section aligned with expected MSc (PT) benchmarks. Applicable domains of the original Assessment of Clinical Performance (e.g., communication, professionalism) aligned with the advanced practice portion of the placement. Reflections included strengths of providing exposure and increased awareness of the APP role and providing a placement to practise core physiotherapy skills. Challenges included lack of standardization of APP roles contributing to difficulties in establishing delegation and expectations in the placement. Conclusions: Awareness of APP roles is limited, particularly among physiotherapy students. Developing student clinical placements in advanced practice roles may increase awareness while supporting clinical education opportunities in entry-level physiotherapy curricula. This case report offers insight into one APP clinical placement experience with recommendations for developing similar placement models.